The career dynamics of high-skilled women and men: Evidence from Sweden - Jim Albrecht; Mary Ann Bronson; Peter Skogmann Thoursie; Susan B. Vroman (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2018)
In this paper, we use matched worker-firm register data from Sweden to examine the career dynamics of high-skill women and men. Specifically, we track wages for up to 20 years among women and men born in the years 1960 - 70 who completed a university degree in business or economics. These women and men have similar wages and earnings at the start of their careers, but their career paths diverge substantially as they age. These men and women also have substantial differences in wage paths associated with becoming a parent. We look at whether firm effects account for the differences we observe between women's and men's wage profiles. We document differences between the firms where men work and those where women work. However, a wage decomposition suggests that these differences in firm characteristics play only a small role in explaining the gender log wage gap among these workers. We then examine whether gender differences in firm-to-firm mobility help explain the patterns in wages that we see. Men and women both exhibit greater mobility early in their careers, but there is little gender difference in this firm-to-firm mobility. We find that the main driver of the gender difference in log wage profiles are that men experience higher wage gains than women do both as "switchers" and as "stayers".
Keywords: J16; J31; 330; Wages; Earnings; Gender gaps; Firms